Strategies for enhancing the sensitivity of plasmonic nanosensors - Guo, Longhua (2016)
Based on the localized surface plasmon resonance (LSPR) of metallic nanoparticles, plasmonic nanosensors have emerged as a powerful tool for biosensing applications. Many detection schemes have been developed and the field is rapidly growing to incorporate new methodologies and applications. Amidst all the ongoing research efforts, one common factor remains a key driving force: continued improvement of high-sensitivity detection. Although there are many excellent reviews available that describe the general progress of LSPR-based plasmonic biosensors, there has been limited attention to strategies for improving the sensitivity of plasmonic nanosensors. Recognizing the importance of this subject, this review highlights recent progress on different strategies used for improving the sensitivity of plasmonic nanosensors. These strategies are classified into the following three categories based on their different sensing mechanisms: (1) sensing based on target-induced local refractive index changes, (2) colorimetric sensing based on LSPR coupling, and (3) amplification of detection sensitivity based on nanoparticle growth. The basic principles and cutting-edge examples are provided for each kind of strategy, collectively forming a unifying framework to view the latest attempts to improve the sensitivity of nanoplasmonic sensors. Future trends for the fabrication of improved plasmonic nanosensors are also discussed.